Project-Based Assessment Models for Senior High School Grade XI - Muryanti, Vivi (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2015)
Project-Based Learning is one of the approaches of teaching English which supports the scientific approach of Curriculum 2013. This approach can bring some benefits to thestudents namely promoting the comprehensible input and output and gaining successfulexperiences with the real world, and also supporting learner centeredness during the learning process. However, the implementation of this approach still has some problems particularly in terms of appropriate kinds of project and the way to assess the students‟ progress andachievement. Therefore, this article proposes the projects and the assessment models forSenior High School Grade XI as an alternative to overcome the problems of theimplementation of Project-Based Learning in Curriculum 2013.Keywords: project-based learning, Curriculum 2013, assessment models, senior high school